Respuesta :

Answer:

x = 1

y = 2

Step-by-step explanation:

y =8x - 6  ---------------------------------(I)

y = 2x -------------------------------------(II)

substitute y = 2x in equation (I)

2x = 8x - 6

Add 6 to both sides

2x + 6 = 8x

Subtract 2x from both sides

6 = 8x - 2x

6 = 6x

Divide both sides by 6

6/6 = x

x = 1

Substitute x = 1 in equation (II)

y = 2*1

y = 2

Since both equations equal to y, that would mean that both equations would equal each other. This means that the equation would turn into 2x = 8x - 6. Once you have this equation, you have to move all the terms that have the pronumeral x to the left. So, you would move 8x to the left. In order to do this, you have to minus 8x on both sides, 2x-8x=8x-8x-6. This is equation will simplify to -6x=-6. To find out what x is equal to, you then need to get rid of the -6 by dividing -6 by both sides. In the end, x should equal to 1. Then you need to find out what y is equal to. Since x=1, you can substitute it into one of the equations. Let’s use the equation y=2x. If you substitute x with 1, y should equal to 2. Now you know what y and x equals to.